Peran Budaya Kaizen dan Reward dalam Meningkatkan Kinerja Karyawan - Tiara Suci Bentar; Acep Samsudin; Nor Norisanti (IPM2KPE, 2019)
The purpose of this study was to find out and analyze the role of kaizen culture and rewards in increasing employee performance at PT. Pos Indonesia (persero) sukabumi. The variables in this study are kaizen and reward culture as independent variables, and employee performance as the dependent variable. Thissstudy usespprimary data in the form of questionnaire answers and secondaryydata through documents. The data analysissmethod used isddescriptive and associative analysis. The research method used in this study is explanatoryyresearch with a quantitativeaapproach. This type of researchhmethod uses a type of non-probability sampling included in the saturated sample. The data analysis technique used is the validity test, reliability test, multiple linear regression analysis, including the test of the coefficient of determination and multiple correlation coefficients.The results of the test coefficient of determination seen from the value (adjusted R2) of 0.251 can be interpreted that the role of kaizen culture and rewards in improving employee performance amounted to 25.1%. The remaining 74.9% is influenced by other factors outside of this study. Based on the multiple correlation coefficient test seen from the R value of 0.532, it shows that there is a moderate relationship between kaizen culture and reward with employee performance. Keywords: Kaizen Culture, Reward, Performance.